La Famiglia Modotti: Transnational Family - Ashley Marie Zampogna-Krug (Diasporas: Circulations, Migrations, Histoire)
This article explores how the Modotti family, despite rarely residing together in one country, maintained a common identity based on shared spaces crafted from correspondence and international political involvement. Their everyday stories challenge the traditional assimilation paradigm and reveal how family bonds fostered activism. In the midst of immigrant restriction and heightened surveillance, the Modottis exemplify how la famiglia transcended boundaries.